2020
DOI: 10.1111/obr.13131
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of metabolic flexibility on metabolic health

Abstract: Glucose, fatty acids, and amino acids among others are oxidized to generate adenosine triphosphate (ATP). These fuels are supplied from the environment (through food intake) and internal depots (through lipolysis, glycogenolysis, and proteolysis) at different rates throughout the day. Complex adaptive systems permit to accommodate fuel oxidation according to fuel availability. This capacity of a cell, tissue, or organism to adapt fuel oxidation to fuel availability is defined as metabolic flexibility (MetF). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 128 publications
(320 reference statements)
2
71
1
Order By: Relevance
“…Finally, the differences in LDL‐C between groups (higher in Mfn2‐LA group) may represent the initial steps toward a disturbed lipid profile mediated by decreases in Mfn2 protein in SM. This could result from a reduced tissular capacity to adapt fuel oxidation to fuel availability, that is, an impaired metabolic flexibility 35 . We have recently shown that healthy subjects with low metabolic flexibility have higher circulating LDL‐C than subjects with high metabolic flexibility 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the differences in LDL‐C between groups (higher in Mfn2‐LA group) may represent the initial steps toward a disturbed lipid profile mediated by decreases in Mfn2 protein in SM. This could result from a reduced tissular capacity to adapt fuel oxidation to fuel availability, that is, an impaired metabolic flexibility 35 . We have recently shown that healthy subjects with low metabolic flexibility have higher circulating LDL‐C than subjects with high metabolic flexibility 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Different Metflex markers have been physiologically related to physical fitness and insulin sensitivity [ 2 , 4 , 6 , 8 , 10 , 13 , 14 , 24 ]. The present study aimed to determine their correlation particularly testing their association with body fatness while controlling for VO 2peak (mL∙kg −1 ∙min −1 ) in subjects with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, this work demonstrates that 46% of TFO’s associated variance is explained by MFO, and the latter shows an inverse relationship with the RER peak ( p < 0.01) and so, MFO is a valid marker of dynamic substrate selection (fueling) during submaximal exercise. Measurement of the fat oxidation increase in response to submaximal exercise is a valid strategy for Metflex assessment [ 2 , 4 ], future studies need to analyze whether MFO, TFO and RER peak are associated with postprandial fat oxidation after a high fat meal and nutrient oxidation during the sleep period, conditions that require Metflex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, up to that date, 8,488,099 cases of coronavirus were registered and, of these, 210,299 died due to this pathology. In the state of Sergipe, according to the State Secretariat, 128,395 cases of infection by SARS-CoV-2 and 2662 deaths were identified, with the first case report of this infection in March of 2020 [4,5].…”
Section: Introductionmentioning
confidence: 99%